Sufism, Spirituality and Sustainability / Rethinking Islamic Mysticism through Contemporary Sociology - Akman, Kubilay (Comparative Islamic studies, 2008)
People are looking for therapeutic ways to deal with the damaging rhythms and handicaps of modern life styles which threaten the physical, social and psychological endurance of human-beings. Reconsideration of "old" philosophies, ancient wisdom and spiritual/mystical paths in a contemporary context was among the solutions that were launched to overwhelm the modern sense of alienation in the second half of 20th Century and this tendency is still going on nowadays at the first decade of the 21st Century. Sufism has been one of the traditions from which modern individuals expected answers to their ontological dilemmas produced in daily life by the society, social relations, media and finally by themselves. The purpose of this paper is to discuss sociologically whether Sufism, the mystical, peaceful and tolerant way of Islam, could be an answer to the social problems of modern societies. What is the social alternative of Sufi traditions regarding the contemporary issues such as: social and technological alienation, sustainable development and environmental/ecological crisis? This paper is an attempt to emphasize the possibilities of Sufism beyond spirituality, with a discussion based on the sociological conception of the subject. (Author abstract)